STUDI KINERJA SIMPANG JALAN PAROS MAMUJU – KALUKKU – JALAN AKSES BANDARA TAMPA PADANG - Imam, Imam Wardani; T, M. Nashir; Kasmaida, Kasmaida (Jurnal Teknik Sipil dan Arsitektur, 2026)
The significant growth in the number of vehicles in Mamuju Regency, West Sulawesi, along with the development of infrastructure such as Tampa Padang Airport and Belang-Belang Port, creates the potential for traffic congestion, especially at the intersection of Jl. Poros Mamuju-Kalukku-Jl. Tampa Padang Airport Access. This study aims to analyze the existing conditions and performance of traffic movements at the unsignalized intersection based on the Indonesian Road Capacity Guidelines (PKJI) 2023. The method used is a quantitative approach through a seven-day traffic survey during peak hours. Data collected included traffic volume, intersection geometry, and environmental conditions around the intersection. Analysis using the Indonesian Road Capacity Guidelines (PKJI) 2023 was conducted on the intersection capacity, and intersection performance. The results showed that the peak hour of vehicles occurred on Monday, May 19, 2025 at 07.00-08.00 a.m. The volume of vehicles was 1111 vehicles / hour or 612.6 smp / hour with a degree of saturation (Dj) 0.20, delay (T) 6.8, queue opportunities (Pa) 2-9%. And on Sunday May 25, 2025 at 10:00-11:00 am, the volume of vehicles was 638 vehicles / hour or 412 smp / hour with a degree of saturation (Dj) 0.14, delay (T) 5.9, queue opportunities (Pa) 1-6%. Performance assessment based on PKJI 2023 parameters provides an overview of the traffic service of the intersection in the level of service (LOS) B category, which means that the traffic flow conditions are good.